Diagnostic and interventional implications of telemedicine in Alzheimer's disease and mild cognitive impairment: A literature review. (15th November 2019) - Costanzo, Maria Cristina; Arcidiacono, Chiara; Rodolico, Alessandro; Panebianco, Mariangela; Aguglia, Eugenio; Signorelli, Maria Salvina
Abstract : Introduction: Worldwide, life expectancy, and aging‐related disorders as mild cognitive impairment (MCI) and Alzheimer disease (AD) are increasing, having a rising impact on patients' quality of life and caregivers' distress. Telemedicine offers many possibilities, such as remote diagnosing and monitoring of patients. Objective: The purpose of this study is to provide a narrative synthesis of the literature about the implementation of telemedicine for diagnosis, treatment, and follow‐up of patients with AD and MCI and their caregivers. Methods: A systematic literature review was conducted on MEDLINE, EMBASE, and the Cochrane Library databases up to September 2018. MCI or AD diagnoses were the conditions of interest. We excluded other dementias. Results: Fifty‐six articles met inclusion criteria. We identified two main categories: diagnosis group (DG) and follow‐up/interventional group (FIG). Fifteen articles suggested how to make a remote or earlier diagnosis: four were case‐control accuracy studies, nine were paired comparative accuracy studies, and two were prospective single‐arm accuracy studies. Among these, four focused on MCI, six on AD, and five on both. Forty one focused on supporting patients during the stages of the disease (28 articles), patient's caregivers (nine articles), or both (four articles). Conclusions: The rising use of telemedicine could actively improve AD and MCI patients' lives, reduce caregivers' burden, and facilitate an early diagnosis if patients live in remote places. However, as some studies report, it is relevant to take into account the emotional impact of telemedicine on patients and not only on the effectiveness.